The British Court and the 1707 Union of England and Scotland - Taylor, Michael (2023)
This is a study in political history which addresses the origins of the Union of England and Scotland in 1707. Unlike most recent scholarship, it does not take a Scottish perspective. It does not however, provide a corresponding study of ‘English’ motives and attitudes. It argues that a bilateral Scotland-England framework is inappropriate and unhelpful for the purposes of understanding the origins of the Union. This is because such a framework fails to accord sufficient agency and autonomy to the monarchy and its closest advisers, or ‘Court group’, after the ‘Glorious Revolution’ and sufficient political coherence to the ‘Union of the Crowns’ that preceded the Union. Such ‘Court groups’ should not, therefore, be conflated with ‘England’ and their motives can be distinguished from ‘English’ motives. It concludes that rather than being the by-product of a politically expedient English parliamentary reaction to political or economic pressure from Scotland, the Union was the outcome of deliberate policy pursued by a Court group comprising Anne and her chief advisers, the Triumvirate of Godolphin, Marlborough and Harley. The origins of this policy lay in William III & II’s recognition that active participation in European great power geopolitics and war, precipitated by the Revolution, demanded greater alignment within the Union of the Crowns. This need was brought home by the profound geopolitical and domestic impact of the Scottish attempt to establish a colony in Darien. Consequently, union initiatives were launched in 1700 and 1702. Just as the geopolitical strategy of resistance to Louis XIV survived William’s death, so this union policy continued into Anne’s reign and was not abandoned after the termination of union negotiations in 1703.